Identification of Differentially Expressed MicroRNAs in Endometrial Cancer Cells After Progesterone Treatment. Issue 4 (1st May 2012) - Bae, Jeehyeon; Won, Miae; Kim, Dae-Yeon; Kim, Jong-Hyeok; Kim, Yong-Man; Kim, Young-Tak; Nam, Joo-Hyun; Suh, Dae-Shik
Abstract : Introduction: The main methods of treatment of endometrial carcinoma are hysterectomy and bilateral oophorectomy with lymphadenectomy. However, another option for hormonal treatment of endometrial carcinoma, the use of progesterone in young patients to preserve childbearing capacity, has been reported, and a high remission rate has been described in well-selected stage I, grade 1 endometrial cancer. Although it is intriguing that hormonal therapy alone can treat endometrial carcinoma without surgery or cytotoxic chemotherapy, the molecular basis for the effects of progesterone on endometrial carcinoma is not clearly known. MicroRNAs (miRNAs) are a class of naturally occurring small, noncoding RNA molecules that control cellular function and are known to function as both tumor suppressors and oncogenes. Thus, in the present study, changes in the miRNA profile of endometrial carcinoma cells on progesterone treatment were studied. Method: To elucidate the mechanism of hormonal treatment in endometrial carcinoma cells, we studied the changes in miRNA expression in endometrial carcinoma cells on treatment with progesterone using the Hec1A endometrial carcinoma cell line as a model system. Hec1A cells were treated with medroxyprogesterone acetate, and total RNA was extracted. The changes in the miRNA profile after progesterone treatment were determined using a microarray containing 868 miRNAs. Results: Of 868 miRNAs, the expression levels of miR-625*, -21, -142-5p, and 146b-5p were increased by more than 400%, whereas the expression levels of miR-633, -29c, -29*, and -193b were decreased by 50%. To validate the array results, quantitative real-time polymerase chain reactions were performed. Conclusions: MiRNA expression was modulated by progesterone treatment in endometrial carcinoma cells, implying a possible critical role of miRNAs in regulating posttranscriptional gene expression on progesterone treatment. Further studies are required to clarify the mechanism involved in the hormonal treatment of endometrial carcinoma.